Effect of the Embolization of Completely Unpurified Islets on Portal Vein Pressure and Hepatic Biochemistry in Clinical Practice - Sung Ho Hyon; María Candela Ceballos; Mariana Barbich; Rosana Groppa; Luis Grosembacher; María Mercedes Vieiro; Laura Barcan; Salomon Algranati; Leon Litwak; Pablo F. Argibay M.D., Ph.D. (Cell Transplantation, 2004)
Here we report on the impact of completely unpurified islet transplantation on the portal vein pressure (PVP) and the hepatic biochemistry in the peritransplant period and on follow-up. Type I diabetic patients underwent simultaneous kidney and islet transplantation. Islets were not purified from the acinar tissue to prevent loss of endocrine mass. Each patient received a mean 521,846 ± 201,539.4 islet equivalents (7812.1 islet equivalents/kg/recipient). Immunosuppression and peritransplant medication were given according to the Giessen protocol. The islets were injected into the left hepatic lobe through the umbilical vein. PVP was recorded at time 0 and every 5 min throughout cell infusion. Liver function was assessed daily for the first 10 days, and on follow-up. Basal, peak, and final PVP were 12 ± 3.8, 25.1 ± 7.9, and 19.5 ± 6.2 mmHg, respectively (basal vs. final, p < 0.05). Bilirubin, alkaline phosphatase, prothrombin time, and APTT stayed within normal range. Peak aspartate aminotransferase (AST), alanine aminotransferase (ALT), and serum amylase were 109.4 ± 61.2 IU/L (basal vs. peak, not significant), 79.5 ± 56.9 IU/L (basal vs. peak, not significant), and 887.5 ± 153.6 IU/L (basal vs. peak, p = 0.02), respectively. In all cases AST, ALT, and amylase normalized within 6 days posttransplant and remained so on follow-up (longest control, 33 months posttransplant). Although the intrahepatic infusion of unpurified pancreatic islets affects both the portal vein pressure and the hepatic biochemical profile, this effect is transient and does not compromise the safety of the procedure.